1955
DOI: 10.1029/tr036i002p00342-2
|View full text |Cite
|
Sign up to set email alerts
|

Discussion of symposium on land erosion “Piping”

Abstract: The present writers are familiar only with the Picacho and San Pedro areas, among those cited by the authors, and therefore limit discussion to the occurrence of earth cracks in these areas. The existence of piping is not questioned, and the five conditions suggested by the authors are a justified explanation in the San Pedro area, for example. It is thought, however, that some of the phenomena described as piping are earth cracks whose origins are governed by factors other than those outlined. Once formed, ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1979
1979
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…With further study, more and more scholars use painstaking 'lines' to describe these earth fissures. They even analysed stratigraphic profiles and found that these earth fissures appear to be dynamic and are more closely related to atmospheric precipitation and groundwater pumping activities (Heindl et al 1955;Pashley 1961;Carpenter 1993). Because these factors affect earth fissures and their characteristics emphasize different aspects, studies on these factors often lead to different judgments on the same geological phenomenon and even opposite conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…With further study, more and more scholars use painstaking 'lines' to describe these earth fissures. They even analysed stratigraphic profiles and found that these earth fissures appear to be dynamic and are more closely related to atmospheric precipitation and groundwater pumping activities (Heindl et al 1955;Pashley 1961;Carpenter 1993). Because these factors affect earth fissures and their characteristics emphasize different aspects, studies on these factors often lead to different judgments on the same geological phenomenon and even opposite conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, however, earth fissures occur in areas of low seismicity (Holzer, 1986). In particular, the Basin and Range province in Arizona is an area of low seismicity (Sumner, 1976 Heindl and Feth (1955) argued against piping as a sole cause of fissuring because drainage of fissures is internal.…”
Section: Physical Settingmentioning
confidence: 99%
“…Heindl and Feth (1955) rejected the piping hypothesis because earth fissures drain internally. Pashley (1961) Correlation of horizontal strain with water-level fluctuations was tested statistically using Pearson correlation coefficients (Sokal and Rohlf, 1969).…”
mentioning
confidence: 99%